2017
DOI: 10.1111/nph.14480
|View full text |Cite
|
Sign up to set email alerts
|

The O‐methyltransferase PMT2 mediates methylation of pinosylvin in Scots pine

Abstract: Heartwood extractives are important determinants of the natural durability of pine heartwood. The most important phenolic compounds affecting durability are the stilbenes pinosylvin and its monomethylether, which in addition have important functions as phytoalexins in active defense. A substantial portion of the synthesized pinosylvin is 3-methoxylated but the O-methyltransferase responsible for this modification has not been correctly identified. We studied the expression of the stilbene pathway during heartw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…However, it should be noted that PsPMT1 showed a relatively broad substrate specificity, methylating several compounds such as stilbene aglycones, flavonoids, and hydroxycinnamic acids, many of these even more efficiently than pinosylvin. In 2017, Paasela and co-workers [134] subsequently isolated and characterized an O-methyltransferase from P. sylvestris (PpPMT2), which is held responsible for the methylation of pinosylvin. Unlike the multifunctional PsPMT1, PsPMT2 preferentially methylated pinosylvin into its monomethyl ether, showing a high degree of specificity for stilbenes.…”
Section: Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that PsPMT1 showed a relatively broad substrate specificity, methylating several compounds such as stilbene aglycones, flavonoids, and hydroxycinnamic acids, many of these even more efficiently than pinosylvin. In 2017, Paasela and co-workers [134] subsequently isolated and characterized an O-methyltransferase from P. sylvestris (PpPMT2), which is held responsible for the methylation of pinosylvin. Unlike the multifunctional PsPMT1, PsPMT2 preferentially methylated pinosylvin into its monomethyl ether, showing a high degree of specificity for stilbenes.…”
Section: Methylationmentioning
confidence: 99%
“…Several studies on Scots pine have shown remarkable increases in pinosylvin and pinosylvin monomethyl ether accumulation following wounding stress, associated with overexpression of PsSTS, as well as of genes coding for O-methyltransferases involved in stilbene methylation (PsMT1 and PsMT2) [134,221,223].…”
Section: Woundingmentioning
confidence: 99%
“… Chaffey (2002) asked ‘Why is there so little research into the cell biology of the secondary vascular system of trees?’ and addressed the lack of funding, techniques and the imparity between primary and secondary cell wall research. Heartwood extractives have been mainly investigated by wet-chemical and chromatographic methods ( Ekeberg et al 2006 ) and recently also genetic approaches ( Paasela et al 2017 ). To investigate extractives in context with microstructure, TOF-SIMS imaging has been applied in Cryptomeria japonica trees and showed that the extractives tend to accumulate near the radial rays ( Saito et al 2008 , Kuroda et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mapping and bioinformatic analyses of gene expression are based on the most complete and high-quality reference transcriptome of P. sylvestris available to date (Ojeda et al 2019). Previous transcriptome studies of P. sylvestris have concentrated on a narrow set of tissues in each study such as wood (Paasela et al 2017), embryo (Merino et al 2016), and needles (Wachowiak et al 2015; Duarte et al 2019) or focused on a limited set of genes (Guseva et al 2020). The present study allows comparison across a wide set of genes expressed in the above-ground parts of adult P. sylvestris trees growing in a natural forest.…”
Section: Resultsmentioning
confidence: 99%